(untitled) (Bangladesh Journal of Medicine, 2022)
Background: Chronic kidney disease (CKD) is a global health problem associated with increased risks of morbidity, premature mortality, and/or decreased quality of life. CKD is usually asymptomatic until progressive damage occurs and produce multiple symptoms and signs. Progressive loss of kidney function in CKD leads to reduced production of 1-á-(OH) 2-D3 (1, 25-dihydroxyvitamin D; calcitriol) and abnormal mineral homeostasis. The aim of the study was planned to assess the mineral and bone disorder in CKD patients admitted in a tertiary care hospital. Methods: A Cross sectional observational study was performed at a tertiary care centre. 100 cases of diagnosed Chronic Kidney Disease patients in indoor of department of Nephrology and Medicine of Sir Salimullah Medical College Mitford hospital from March 2018 to August 2018 were included in this study. Results: Majority of the patients (60%) were of age between 46 and 65 years. 31% of the study population were older than 65 years. 72% of the study population were male and 28% were female. Diabetic nephropathy was the leading cause of CKD, affecting 36% of the study population. Hypertension was the likely cause in 26% of the subjects. Obstructive uropathy and chronic glomerulonephritis affected 7% and 5% of the subjects respectively. There was one (1%) patient with ADPKD, and in 25% of the cases no causative factor was identified. Most (40%) of the study subjects were in the stage 3 of CKD. 34% & 26% of the patients were in the stage 5 & 4 respectively. We did not find any patient with normal vitamin D level. 10% of the patients were in the insufficient range and 90% of the study subjects were deficient in vitamin D. Hyperparathyroidism was prevalent in 75% of the study subjects. 79% of the patients had elevated serum phosphate levels. Hypocalcemia was found in 49% of the patients. 33% of the patients had hyperkalemia during admission. Hyperphosphatasia was prevalent in 39% of the study subjects. However, bone fraction of the ALP was not tested. Among stages 3B, 4 and 5 CKD patients, there were 2% patients in each group that were insufficient in vitamin D. Majority (32% in stage 5, 24% each in stages 3B and 4) were deficient in vitamin D. Deficiency was also prevalent in earlier stages of CKD (10% patients in stage 3A). The difference was statistically significant, that is, the later the stage of CKD the greater the prevalence of vitamin D deficiency was. All the patients in stage 5 and 4 (34% and 26% respectively) had hyperparathyroidism. 0% and 15% of the patients in stages 3A and 3B respectively had hyperparathyroidism. The difference between groups was statistically significant. Serum calcium level correlated well with the stage of CKD. Most of the patients in stage 5 were hypocalcemic (32 among 34). Among the 39% of the total study population with hyperphosphatasia, 24%, 9% and 6% were in stages 5, 4 & 3B respectively. Which were statistically significant. 49% pf the patients had hyperparathyroidism with hypocalcemia, 26% of the patients had hyperparathyroidism and normal serum calcium levels. None of the patients had hypocalcemia and normal PTH level. Among the 90 patients with deficient vitamin D levels, 46 had hypocalcemia also. 70 patients with deficient vitamin D level also had high PTH level. The difference between groups which was statistically significant. Conclusion: MBD is a common complication in our CKD patients. Raised PTH, low 25(OH) D, and raised phosphorus levels were the most prevalent markers. Majority of our patients presented, or were referred late. Clinical features of MBD in CKD were poor guides to the presence of MBD in our pre-dialysis patients. Bangladesh J Medicine 2022; 33: 145-153